Considerations Regarding the Strategic Mission- Stockholders; Equity Relationship, Cash Flows, and their Effects on Stakeholder Remuneration (Global Journal of Management and Business Research, 2022)
The development of the following article aims to identify the relationships between the strategic mission and the stockholders' equity of the company, the cash flows that are generated from this interaction, and the effects on the remuneration received by the stakeholders of the entity. This time the analysis will focus on dividends paid to shareholders, although aspects of some income from other entities involved in the business process are pointed out, such as employee salaries. For these purposes, an analysis of the relationships between the mission of the strategic plan and the financial funds flows of the selected entities was developed, based on the study of the companies Tesla, Inc., General Motors, Inc., Ford Motors Company, Google Inc., Apple Inc., Facebook, Amazon, and Hertz. The data collection technique was constituted by the documentary research to later establish a study of the links and relationships existing between the interested parties in the companies. This is how it was possible to detect an interaction between the variables mission, flow of financial funds, dividends to shareholders, and salaries of employees.
Keywords: strategic mission; stockholders' equity; financial cash flows; stakeholder remuneration